AN EXPERIENCE OF SERELAXINE USE FOR ACUTE HEART FAILURE IN PATIENTS WITH ONCOHEMATOLOGICAL DISEASES - L. A. Shpagina; L. A. Panacheva; E. M. Loctin; O. S. Pospelova; V. N. Kotova; V. N. Kokhno; А. А. Rukavitsina (Кардиоваскулярная терапия и профилактика)
Treatment of acute heart failure (ACF) remains a strenuous task. Modern treatment methods — diuretics, vasodilators, inotropic drugs — are effective in ACF symptoms reduction, but do not decrease risk of death, that is still very high in this urgent condition. This determines a necessity of novel treatment methods search.Aim. To assess efficacy of serelaxine in ACF caused by cardiotoxic effect of cytostatic therapy.Material and methods. Serelaxine is a recombinant human relaxine-2, having hemodynamic and pleiotropic organoprotective effects. The data on the drug efficacy for one or other cause of ACF is non-sufficient. In single-center observational study there is an experience presented of serelaxine in pulmonary oedema, developed as complication of polychemotherapy (PCT) in oncohematological diseases.Results. The use of serelaxine in addition to the standard treatment led to successful cessation of pulmonary oedema, stabilization of hemodynamics and of blood gases, therefore to completion of full PCT program.Conclusion. The first clinical experience presented has shown efficacy of serelaxine in ACF due to cardiotoxic action of PCT in oncohematological patients. Further clinical trials are aimfull in this category of patients.